COD Removal and Biodegradability Enhancement of Pharmaceutical Wastewater Using a Multilayer Internal Electrolysis Reactor - Liang, Sun; Can, Wang; Min, Ji; Xiao Fang, Liu (Asian Journal of Chemistry, 2011)
A multilayer internal electrolysis reactor treating actual pharmaceutical wastewater was established to evaluate the ecological safety and feasibility of internal electrolysis processes. Our findings showed that about 20 % COD of the pharmaceutical wastewater was removed by the internal electrolysis reactor. The COD removal efficiencies increased initially and then decreased with the increase in influent concentrations. The best COD removal was observed at pH 4. Additionally, injection of air into the reactor can promote COD removal compared with nonaeration conditions. All hB/C and hROUR values under every condition were positive, which indicated the enhancement effects on the wastewater biodegradability after treatment. The effects of influent COD concentrations on hB/C and hROUR showed a similar trend with that of COD removal, suggesting that the biodegradability enhancement was mainly caused by COD removal in wastewater. High pH helped to improve the wastewater biodegradability while aeration lowered the biodegradability enhancements.